Biomechanical changes of the oral and craniofacial regions as a result of altered breathing patterns - R. Jordaan; M. Papadopoulos (AOSIS, 2001)
The purpose of this report is to discuss the biomechanical changes in the oral and craniofacial regions as a result of altered breathing patterns. The increase in air pollution and allergens, resulting in allergic reactions, is often the cause of chronic nasal obstruction. The biomechanics of the oral, cranial and facial areas are intimately linked, and will be adversely affected by any change in the breathing pattern. As a result of nasal obstruction, the biomechanics of respiration changes to facilitate mouth breathing, and the resting position of the tongue and mandible is disrupted. The lips are parted, the freeway space and craniocervical angulation increase. The muscle activity of the posterior cervical musculature, anterior temporalis and suprahyoid muscles will be increased. The equilibrium of forces in the oral and craniofacial region is disturbed, and these abnormal forces could lead to the development of "adenoid facies", malocclusions and dysfunction over a period of time. It is important to diagnose chronic nasal obstruction and mouth breathing early and start treatment before the negative effects of the musculoskeletal system occur. A sound understanding of the biomechanical changes will enable the physiotherapist to carry out a skilful examination and plan a treatment program, based on informed decisions.